Utilization of AHP and MCDM Integrated methods in Urban Project Management (A Case Study for Eslamshahr-Tehran) - Touti, Elham; Pourghader Chobar, Adel (International journal of industrial engineering and operational research, 2020)
Project management is considered as one of the most important indicators of project management in civil projects that has tried to take into consideration the different managerial, social, operational, executive and environmental aspects in order to advance the project goals especially. Use in urban areas. In the meantime, some factors are effectively involved in determining the different conditions and methods of project implementation and management in urban areas that are of significant importance in decision making, promotion or stopping work. Multi-criteria decision-making (MCDM) and hierarchical decision-making (AHP) approaches are used today to meet multiple goals. In this study, using the integrated approach including MCDM and AHP methods, we tried to evaluate the effective factors in urban projects for Eslamshahr city of ​​Tehran. For this purpose, by identifying the effective factors in the city's development projects, extracted from the 10 infrastructure projects of the city, the project design criteria and sub-criteria are determined at the management and implementation levels. Then, these criteria are evaluated according to the importance and sensitivity of the different projects prioritized on the effectiveness of each in Eslamshahr urban projects.